Intellectual Dimensions of Post-Colonialism and Identity in the Context of Urdu Novel - Irum, Saeeda; Saba, Mehreen (Makhz (Research Journal), 2024)
Post-colonialism is literary ideology to analyze and examine different perspectives and the consequences of colonial domination on the cultures, societies, and identities of the subjected bio contents. It tries to answer the question of why and how identities are constructed within colonial histories and how those notions are contested and transformed. Identity in postcolonialism has several intellectual and rational dynamics and dimensions. In this research article, an effort has been made to study these dimensions with special reference to different genres of Urdu Literature i.e. Novel, Short Story and Poetry etc.